Formulasi biskuit tepung tempe biji kedawung (Parkia roxburghii G. Don) untuk pasien diabetes melitus - Triyanto, Bagaskara Putra; Nugroho, Teddy Wahyu; Widyastuti, Nurmasari; Masruroh, Zulfatul; Anjani, Gemala (Jurnal Gizi Klinik Indonesia, 2023)
Formulations of biscuits from kedawung seed tempeh flour (Parkia roxburghii G. Don) for diabetes mellitus patientsBackground: Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia. Blood glucose can be controlled with food consumption with low glycaemic index (GI) and glycaemic load (GL) values. Kedawung seeds contain high protein and fiber and can be an alternative to low GI and GL food sources for DM patients. Objectives: This research analyzed total protein, crude fiber, glycaemic index, and glycaemic load levels from biscuits by substituting kedawung seed tempeh flour.Methods: The study was an experimental study with four treatments. The substitution of kedawung seed tempeh flour in biscuits was 0%, 10%, 30%, and 50%. Protein content was analyzed using the Kjeldahl method, and crude fiber was analyzed using the gravimetric method. Statistical analysis was done using the One Way ANOVA and Tukey posthoc test. A hedonic test on 25 semi-trained panelists was conducted to determine the best formulation, and the results were analyzed using the Kruskal Walls and Friedman post-hoc test. IAUC analyzed the glycaemic index from 10 respondents. Results: Biscuits substituting kedawung seed tempe flour affected protein content (p=0.00) and crude fiber (p=0.00). The best acceptance was biscuits with a 10% substitution of kedawung seed tempeh flour, which has a 32.28% glycemic index value and a 9.98% glycemic load. Conclusions: The biscuits substituting kedawung seed tempeh flour significantly increased protein and crude fiber content. Biscuit formulation with 10% kedawung seed tempeh flour had a low glycemic index and glycemic load.